1977
DOI: 10.1113/jphysiol.1977.sp011689
|View full text |Cite
|
Sign up to set email alerts
|

Ballistic contractions in man: characteristic recruitment pattern of single motor units of the tibialis anterior muscle.

Abstract: SUMMARY1. Single motor units were recorded with highly selective electrodes from intact tibialis anterior muscle in the adult man. A detailed parametric analysis was made of the discharge patterns during voluntary isometric contractions of different peak forces carried out at various rates of force development.2. During the smooth tracking of a ramp force, the different motor units recorded from a given muscle site were recruited in a consistent order, each unit becoming active when the muscle developed a cert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
306
5
3

Year Published

1981
1981
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 480 publications
(340 citation statements)
references
References 24 publications
26
306
5
3
Order By: Relevance
“…This theory predicts recruitment of units from smallest to largest (Desmedt and Godaux, 1977;Veale, 1978). Departures in recruitment order have been identified due to nonphysiological stimuli (Garnett and Stephens, 1981;Semmler and Türker, 1994), changes in rate of force change, and in some voluntary tasks (Thomas et al, 1978;ter Haar Romeny et al, 1982;Riek and Bawa, 1992;Butler et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…This theory predicts recruitment of units from smallest to largest (Desmedt and Godaux, 1977;Veale, 1978). Departures in recruitment order have been identified due to nonphysiological stimuli (Garnett and Stephens, 1981;Semmler and Türker, 1994), changes in rate of force change, and in some voluntary tasks (Thomas et al, 1978;ter Haar Romeny et al, 1982;Riek and Bawa, 1992;Butler et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the rate of rise of the integrated EMG activity reflects the rate of recruitment of motor units, as well as of the increase in their firing frequency, while the peak of the integrated EMG activity is an expression of the total number of units recruited and of their maximum firing frequency [30]. Thus, EMG recordings of expiratory muscle output during cough can provide insights into the neural mechanisms activated during voluntary and reflex cough and during the ER.…”
Section: Muscular Activitymentioning
confidence: 99%
“…It is widely agreed that the recruitment order of motor units recorded during voluntary muscle contraction in man is fixed in that it cannot be altered at will, nor is it different during different sorts of fast ballistic or slow ramp contractions (Denny-Brown & Pennybacker, 1938;Tanji & Kato, 1973;Bfidingen & Freund, 1976;Desmedt & Godaux, 1977a, 1978. In spite of the known specialization of motor unit mechanical properties within individual muscles, the controlling motoneurone pool and its input would appear to be organized in such a way as to prevent rather than allow the potentially useful selective activation ofunits according to mechanical type.…”
Section: Introductionmentioning
confidence: 99%